Flowers of allium cepa l. as nutraceuticals: phenolic composition and anti-obesity and antioxidant effects in caenorhabditis elegans - Moliner, Cristina (2018)
Allium cepa L., commonly known as onion, is one of the most-consumed vegetables. The benefits of the intake of its bulb are well studied and are related to its high polyphenol content. The flowers of onions are also edible; however, there are no studies about their biological properties. Our aim was to determine the polyphenolic profile and assess the antioxidant and anti-obesity capacity of an ethanolic extract from fresh flowers of A. cepa. The phenolic constituents were identified through LC-DAD-ESI/MSn. For the anti-obesity potential, the inhibitory activity against digestive enzymes was measured. Several in vitro assays were carried out to determine the antioxidant capacity. A Caenorhabditis elegans model was used to evaluate the effect of the extract on stress resistance and fat accumulation. For the first time, kaempferol and isorhamnetin glucosides were identified in the flowers. The extract reduced fat accumulation in the nematode and had a high lipase and alpha- glucosidase inhibitory activity. Regarding the antioxidant activity, the extract increased the survival rate of C. elegans exposed to lethal oxidative stress. Moreover, the activities of superoxide dismutase and catalase were enhanced by the extract. Our results demonstrate, for the first time, the antioxidant and anti-obesity activity of onion flowers and their potential use as functional foods and nutraceuticals.